2010
DOI: 10.1007/s00335-010-9310-6
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for human hearing loss DFNB30 due to loss of function of myosin IIIA

Abstract: The motor protein myosin IIIA is critical for maintenance of normal hearing. Homozygosity and compound heterozygosity for loss-of-function mutations in MYO3A, which encodes myosin IIIA, are responsible for inherited human progressive hearing loss DFNB30. To further evaluate this hearing loss, we constructed a mouse model, Myo3a(KI/KI), that harbors the mutation equivalent to the nonsense allele responsible for the most severe human phenotype. Myo3a(KI/KI) mice were compared to their wild-type littermates. Myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 27 publications
1
35
1
1
Order By: Relevance
“…1 B), suggesting that OHC function was not impaired. Together, these results are consistent with late-onset, mild hearing loss in Myo3a −/− mice, reminiscent of the hearing loss in Myo3a KI/KI mice (Walsh et al, 2011). In contrast, the ABR thresholds and the DPO AE thresholds and amplitudes of Myo3b −/− mice measured between 2 and 4 mo showed no statistically significant difference compared with those of control mice (P > 0.1; Fig.…”
Section: Resultssupporting
confidence: 84%
“…1 B), suggesting that OHC function was not impaired. Together, these results are consistent with late-onset, mild hearing loss in Myo3a −/− mice, reminiscent of the hearing loss in Myo3a KI/KI mice (Walsh et al, 2011). In contrast, the ABR thresholds and the DPO AE thresholds and amplitudes of Myo3b −/− mice measured between 2 and 4 mo showed no statistically significant difference compared with those of control mice (P > 0.1; Fig.…”
Section: Resultssupporting
confidence: 84%
“…MYO3A was found to play a role in maintaining stereocilia ultrastructure as the DFNB30 mouse displays age-dependent stereocilia degeneration (12). Our working hypothesis is that the localization and activity of class III myosins play a role in transport within actin bundle protrusions.…”
Section: Discussionmentioning
confidence: 91%
“…ESPN1 contains WH2 activity, which binds actin monomers and promotes filament elongation. Disruption of the MYO3A gene is associated with nonsyndromic deafness (DFNB30) (11), and a mouse model of DFNB30 results in age-dependent degeneration of the stereocilia of inner ear hair cells (12). Therefore, characterizing mechanisms of MYO3 motor and kinase regulation are critical for understanding its role in sensory cells.…”
mentioning
confidence: 99%
“…The UK10K study also suggested that reported estimates of disease variant penetrance were too high (16). These findings have increasing relevance as exome and genome sequencing move into population scale surveys for example we observed adults with a GJB2 knockout (p.Trp77Ter, a published deafness risk variant (17)) without any symptoms of hearing loss, and a MYO3A knockout without any symptoms of hearing loss and with normal audiometry (18,19).…”
mentioning
confidence: 90%